Membangun Etika dan Tanggung Jawab Siswa Sekolah Menengah Atas Untuk Menghindari Tindak Pidana Cyber (Hoaks, Ujaran Kebencian, Pencemaran Nama Baik) - Marwenny, Elwidarifa; Wahyuni, Sry; Fauzi, Engrina; ., Gustafianof; Yufiandra, Defika; Somaliagustina, Desi; Citra, Helfira; ., Harniwati; Syafwar, Robi; Utami, Rahmides; ., Nopaluwis; Agustiani, Tri; Mardhatillah, Annisa; Nauval, Ariq (LPPM Universitas Dharma Andalas, 2025)
This community service activity was conducted in several senior high schools in Padang with the aim of increasing students’ awareness and understanding of ethical and responsible social media use to prevent cybercrimes such as hoaxes, hate speech, cyberbullying, defamation, and identity theft. The topic was selected due to the growing number of digital violations involving teenagers and the urgent need for digital literacy education. The method used consisted of interactive socialization sessions supported by pre-test and post-test evaluations, discussions, and educational materials related to digital ethics and the Electronic Information and Transactions Law (UU ITE). The results showed a significant improvement in students’ understanding and awareness after the activity. This indicates that educational and participatory approaches are effective in shaping wiser online behavior among students and can serve as a preventive effort against legal problems in the digital environment.